Estimator Spline Truncated of Semiparametric Regression Estimator Regresi Semiparametrik Spline Truncated - Narita Yuri Adrianingsih (Peneliti.net, 2022)
Semiparametric regression is a combination of parametric and semiparametric regression. This regression is used on data whose pattern is known and partially the pattern is unknown. Ordinary Least Square (OLS), Maximum Likelihood Estimation (MLE), and Penalized Least Square (PLS) can be used to obtain Spline Truncated semiparametric regression curve estimators. This paper will explain about the use of Ordinary Least Square (OLS) to obtain a Spline Truncated Semiparametric Regression estimator